Cost Analysis of Additional Construction Time for the Office Building of the Religious Court of Trenggalek Regency East Java - Widyaningsari, Nidya; Tjendani, Hanie Teki; Sajiyo, Sajiyo (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study investigates the cost implications of accelerating the construction of the Trenggalek Religious Court Office Building in response to delays caused by flooding. Utilizing the crashing method, two acceleration strategies were evaluated: adding overtime hours and increasing workforce. The results indicate that reducing the project duration from 240 days to 180 days through overtime incurs a cost increase primarily due to additional pay, while reducing it to 170 days by adding workers results in higher labor costs. Detailed analysis of durations, costs, and cost slopes for each activity provides valuable insights for project managers to select the most cost-effective acceleration approach. Additionally, a comparative analysis of normal and crashing schedules for various construction tasks highlights potential efficiencies in scheduling and budgeting, ultimately aiding in timely project completion within optimized costs.